The End of the Tory War on Single Parents? - Swift, A; Brighouse, H (Wiley Blackwell, 2007)
Conservative leader David Cameron has faced a wealth of criticism over his controversial views on marriage, largely from the progressive centreleft. Political philosophers Harry Brighouse and Adam Swift argue that this misses the point: Cameron's position is really a radical step forward for the Conservatives